2017
DOI: 10.2136/vzj2016.10.0101
|View full text |Cite
|
Sign up to set email alerts
|

Porous Media Characterization to Simulate Water and Heat Transport through Green Roof Substrates

Abstract: Core Ideas Hydrodynamic and thermal properties of five green roof substrates were determined. Coupled heat and water transport in a hypothetical roof was simulated. The green roof substrates showed a large capacity to store and transport water. Water retention, storage, and organic matter control substrate hydraulic behavior. Green roofs integrate vegetation into buildings, thereby minimizing energy requirements and water runoff. An understanding of the processes controlling water and heat fluxes in green ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 56 publications
2
32
0
1
Order By: Relevance
“…Green roofs have been extensively adopted over the last few decades as a technological solution for sustainable development [1][2][3], as they integrate vegetation into buildings to minimize some negative impacts of urbanization [2][3][4][5]. A properly designed green roof can reduce pollution, noise levels, building energy consumption, and stormwater runoff [2,6,7]. At the same time, green roofs increase biodiversity and provide ecological services in urban environments [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green roofs have been extensively adopted over the last few decades as a technological solution for sustainable development [1][2][3], as they integrate vegetation into buildings to minimize some negative impacts of urbanization [2][3][4][5]. A properly designed green roof can reduce pollution, noise levels, building energy consumption, and stormwater runoff [2,6,7]. At the same time, green roofs increase biodiversity and provide ecological services in urban environments [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Green roof overall performance strongly relies on the interaction between environmental conditions and the green roof's biophysical components [2,5]. A systematic comprehension of the processes occurring in every component of a green roof, under site-specific conditions, is required to understand the benefits described above.…”
Section: Introductionmentioning
confidence: 99%
“…In the European market, mixtures usually contain a small fraction of biological material, in concordance with the guidelines of Forschungsgesellschaft Landschaftsentwicklung–Landschaftsbau (2008), whereas in some North American regions, soilless mixtures containing a much higher proportion of organic matter (OM) are being used (Hill et al, 2016). The organic content is frequently needed to provide nutrients to support plant growth, and the biological material is typically lighter weight (Sandoval et al, 2017). However, the use of large quantities of biological material in green roof media has been associated with the leaching of excess nutrients in runoff water (Czemiel Berndtsson, 2010; Van Seters et al, 2009), and these media have been observed to shrink (Schindler et al, 2016) and become hydrophobic (Raviv et al, 2008b) when dried.…”
mentioning
confidence: 99%
“…There have been many laboratory studies describing the hydraulics of planting media for green roof applications (Babilis and Londra, 2011; Dal Ferro et al, 2014; Poë et al, 2015; Sandoval et al, 2017). Although these studies have focused on particle size and interparticle pore spaces, there remains a paucity of data regarding the hydraulic functions of coarse aggregates with intraparticle porous networks (Raviv et al, 2008b; Stovin et al, 2015), although data are emerging from a few nursery horticulture (Schindler et al, 2016) and green roof (Dal Ferro et al, 2014; Graceson et al, 2013a; Latshaw et al, 2009) research communities.…”
mentioning
confidence: 99%
“…Thus, they were maintained at optimum conditions from January through May 2017. The substrate used was composed of humus, vegetal soil and perlite [16,35]. Due to the requirement of Photosynthetically Active Radiation by the vegetation, 2.5 kWh•m −2 •day −1 of radiation was generated inside the test room.…”
Section: Experimental Site and Setupmentioning
confidence: 99%